2015
DOI: 10.1377/hlthaff.2015.0365
|View full text |Cite
|
Sign up to set email alerts
|

Key Features Of Peer Support In Chronic Disease Prevention And Management

Abstract: Peer support from community health workers, promotores de salud, and others through community and health care organizations can provide social support and other assistance that enhances health. There is substantial evidence for both the effectiveness and the cost-effectiveness of peer support, as well as for its feasibility, reach, and sustainability. We discuss findings from Peers for Progress, a program of the American Academy of Family Physicians Foundation, to examine when peer support does not work, guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 31 publications
3
91
0
2
Order By: Relevance
“…4 In contrast to the eHealth model, peer support delivers highly personalized and engaging support to people at all levels of need. 5 Importantly, this includes the ability of peer support to (1) reach and engage those who are often ''hardly reached'' by clinical and preventive services, and (2) reduce emotional and psychosocial distress among those with chronic conditions and the avoidable acute and hospital care that so often accompany it. 5 Studies have documented the effectiveness, feasibility, and wide acceptability of peer support for chronic disease management and prevention in diverse settings and populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In contrast to the eHealth model, peer support delivers highly personalized and engaging support to people at all levels of need. 5 Importantly, this includes the ability of peer support to (1) reach and engage those who are often ''hardly reached'' by clinical and preventive services, and (2) reduce emotional and psychosocial distress among those with chronic conditions and the avoidable acute and hospital care that so often accompany it. 5 Studies have documented the effectiveness, feasibility, and wide acceptability of peer support for chronic disease management and prevention in diverse settings and populations.…”
Section: Introductionmentioning
confidence: 99%
“…5 Importantly, this includes the ability of peer support to (1) reach and engage those who are often ''hardly reached'' by clinical and preventive services, and (2) reduce emotional and psychosocial distress among those with chronic conditions and the avoidable acute and hospital care that so often accompany it. 5 Studies have documented the effectiveness, feasibility, and wide acceptability of peer support for chronic disease management and prevention in diverse settings and populations. 2,5 With the engagement of peer support and the reach of eHealth (and the effectiveness and feasibility of both approaches), we therefore ask: Can we integrate the high tech of eHealth with the soft touch of peer support to manage the health of populations?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Simoni [95] did not find that in-person peer support groups enhanced ART adherence. However, a review published in 2014 found significant benefits of peer support interventions for other chronic diseases [96]. In a review of stress management interventions for persons living with HIV [97], peer support was a critical component of interventions.…”
Section: Peer Support Via Social Mediamentioning
confidence: 99%
“…1,2 Coaches focus on helping patients to identify goals, create plans to make changes, and implement changes. Although health coaching can be performed by licensed professionals including nurses, physical therapists and respiratory therapists, 3,4 or by other patients (peer support), [5][6][7][8] medical assistants 1,9,10 and other unlicensed health workers (eg, community health workers, lay health advisers, and promotoras) [11][12][13][14][15][16] are emerging as a common and relatively economical workforce that may meet the demand for self-management support. Health coaching has been proposed as an inexpensive and effective means to improve control of chronic conditions 1 and has been effective in improving management of diabetes and other risk factors for cardiovascular disease, asthma, and chronic obstructive pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%